On the separation of executive and legislative powers: Executive independence, liberty, and social welfare. (October 2021) - Fox, Justin; Polborn, Mattias
We explore the effects of a particular facet of separation of powers—namely, the executive's independence from the legislature—on maintaining a norm of legislative restraint in which antagonistic factions refrain from passing laws that infringe on their rival's liberties. Our main result establishes that executive independence may sometimes undermine and at other times facilitate legislative restraint, depending on the probabilities with which the factions hold legislative and executive power. Our results contribute to the larger game-theoretic literature exploring the effects of political institutions; our results also contribute to the literature exploring how institutions designed to protect liberty affect tacit cooperation among rival factions.